Development of a Web-Based Agricultural E-Marketplace Using Laravel - Agustin Setiyorini; Jeffry Andhika Putra; Muhammad Febriyansyah; Venesse Kaylasha Alvino Putri (Universitas Multimedia Nusantara, 2025)
The agricultural sector plays a vital role in Indonesia's economic structure and food security, yet rural farmers often face significant challenges regarding market access and long, detrimental distribution chains. This study aims to design and build a web-based e-marketplace system that facilitates direct transactions between farmers and buyers to cut off conventional distribution lines. The system development method used is the Waterfall model, which includes requirements analysis, system design, implementation, and testing phases. The system was built using the PHP programming language with the Laravel framework for the back-end and MySQL for database management. The results indicate that the developed platform successfully provides features for managing products, categories, orders, and real-time sales reports. Based on Black Box testing on 10 main functional scenarios, the system proved valid and operated according to user specifications without functional errors. In conclusion, this e-marketplace is effective as a technological solution to expand the market reach of local farmers and increase the efficiency of agricultural product transactions.